The Authority of Religious Courts and Religious Affairs Offices on the Issue of Marriage and Divorce Recording After the Publication of the Indonesian Minister of Home Affairs ‘Regulation Number 108 of 2019 - Arif Wisnu Wardhana; Dea Justicia Ardha; Febrina Hertika Rani (Universitas Muhammadiyah Sumatera Utara, 2023)
Marriage and divorce registration issues are specifically mentioned in Law Number 16 of 2019, which amends Law Number 1 of 1974 on marriage, however there remains ambiguity. How is the jurisdiction of religious courts on the matter of marriage and divorce registration following the publication of the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 108 of 2019? is the formulation of the problem in this study. Empirical legal research is the type of research that is conducted. Based on findings, research indicates that religious courts and religious affairs offices have the authority to prohibit marriage and divorce registration issues. Due to alleged uncertainty, its jurisdiction has been reduced since the Minister of Home Affairs of the Republic of Indonesia issued Regulation Number 108 of 2019. Religious courts perform judicial duties and provide rulings or decisions as their final output. While the power of the government is responsible for the administration of the marriage industry